Barriers to Online Learning during the Covid-19 Pandemic at Universities in Poland - Emilia MAZUREK (Communications of International Proceedings, 2021)
The article presents research on the online education during the Covid-19 pandemic at universities in Poland. The aim of the study was to identify barriers to online learning in students’ opinion. The long-term study was conducted in two stages: in June 2020 and in February 2021. Due to the epidemiological limitations, the data was collected using online questionnaires. The presented research was carried out in Poland, on a group of 290 participants (including 201 women and 89 men) who were studying in various types of universities. The measures taken due to Covid-19 have had an immediate effect on higher education and the situation of students. The analysis of collected data made it possible to distinguish five categories of barriers to online learning during the Covid-19 pandemic at universities: organizational and institutional, technical, social, emotional, competence. They show the complexity of the situation in which students have found themselves due to the global health crisis. The findings of the study may be helpful in better preparation of higher education institutions for online education in the future and in planning support for students learning remotely. Building competences useful for self-regulated learning seems to be particularly important.
Keywords: barriers to online learning; Covid-19 pandemic; higher education.